Study and Design Optimization of Fiber Bragg Grating Based Wind Pressure Sensor. (8th June 2015) - Dan, Danhui; Xiao, Rong; Bai, Wulong; Wen, XueLei
A Fiber Bragg Grating (FBG) based wind pressure sensor (WPS) for structural surfaces is introduced, and wind pressure-strain conversion model as well as temperature compensation method is established. By using finite element analysis, the design of the wind-bearing carrier of the WPS is optimized such that the nominal measured values by the FBGs are maximized under the action of fundamental wind pressures suggested in codes. Furthermore, sensing characteristics of the WPS, as well as its static wind safety, pressure stability, and dynamic stability during operation, are investigated. Results demonstrate that the design scheme for the WPS, which is of good object sensing properties and working performance, is technically feasible. The final prototype of WPS is developed according to the proposed optimized design scheme.